Temple door frame at Harshnath Temple - Temples of India Project Team (Jio Institute, 2024)
The doorway of the garbhagriha consists of five panchashakha (jambs) of the Harshnath Temple. Pairs of dvarapala (door guardian) and river goddesses (Ganga-Yamuna) occupy their standard positions at the bottom of the jamb. Mithuna figures are carved on either side in their typical positions. In the foreground are elaborately carved pillars with purna-ghatas, which, according to Art historian Ambika Dhaka, maybe a later replacement.